A Streamlined Protocol for Wheat (Triticum aestivum) Protoplast Isolation and Transformation With CRISPR-Cas Ribonucleoprotein Complexes - Brandt, Kali M.; Gunn, Hilary; Moretti, Nathalia; Zemetra, Robert S. (Frontiers in Plant Science, 2020)
The genetic engineering method CRISPR has been touted as an efficient, inexpensive, easily used, and targeted genetic modification technology that is widely suggested as having the potential to solve many of the problems facing agriculture now and in the future. Like all new technologies, however, it is not without challenges. One of the most difficult challenges to anticipate and detect is gene targets that are inaccessible due to the chromatin state at their specific location. There is currently no way to predict this during the process of designing a sgRNA target, and the only way to detect this issue before spending time and resources on full transformations is to test the cleavage ability of the sgRNA in vivo. In wheat, this is possible using protoplast isolation and PEG transformation with Cas9 Ribonucleoprotein complexes. Therefore, we have developed a streamlined protocol for testing the accessibility of sgRNA targets in wheat. The first steps involve digesting wheat leaf tissue in an enzymatic solution and then isolating viable protoplasts using filters and a sucrose gradient. The protoplasts are then transformed using Cas9 Ribonucleoprotein complexes via PEG-mediated transformation. DNA is isolated from the CRISPR-transformed protoplasts and PCR is performed to amplify the gene target region. The PCR product is then used to assess the transformation efficiency of the chosen sgRNA using Sanger sequencing. This simplified protocol for the isolation and transformation of wheat protoplast cells using Cas9 Ribonucleoprotein complexes streamlines CRISPR transformation projects by allowing for a fast and easy test of sgRNA accessibility in vivo.